Hybrid expert system of rough set and neural network - Yahia, Moawia Elfaki; Mahmod, Ramlan (Faculty of Computer Science and Information Technology, University of Malaya, 1999)
The combination of neural network and expert system can accelerate the process of inference, and then rapidly produce associated facts and consequences. However, neural network still has some problems such as providing explanation facilities, managing the architecture of network and accelerating the training time. Thus to address these issues we develop a new method for pre-processing based on rough set and merge it with neural network and expert system. The resulting system is a hybrid expert system model called a Hybrid Rough Neural Expert System (HRNES).